Maulana Azad as a Poetical and Linguistic Critic - Muhammad Aslam; Dr Abdul Sattar malik (Zaban-o-Adab, 2024)
Sir Syed Ahmad Khan, along with the Urdu elements Pentarchy, including Maulana Muhammad Hussain Azad, Deputy Nazir Ahmad, Allama Shibli Nomani, and Maulana Altaf Hussain Hali, collaborated to strive for the goals of the Ali Garh Movement. Among the Urdu Pentarchy, Maulana Muhammad Hussain Azad stands out individually. He experimented with various aspects of literature in a unique style, initiating prose criticism and prose poetry. He laid the foundation of modern poetry in the mushairas of Anjuman Punjab, and also excelled in tazkira writing as well. His renowned work on tazkira writing and criticism includes the book "Ab-e Hayat." Additionally, he contributed to linguistics with "Sakhan Daan-e-Faars," which deals with linguistics. In his essays and letters, he demonstrated his critical and linguistic insight. This article discusses Ab-e Hayat, Sukhan Daan-e-Faars and the essays and letters of Maulana Azad.